INTERACTIVE APPROACHES IN THE ELT CLASSROOM: A CONCEPTUAL STUDY IN THE EDUCATIONAL INSTITUTES OF BANGLADESH - Ahmed, Md. Kawser; Hossain, Kazi Imran (American International Journal of Social Science Research, 2023)
In an effort to foster a positive learning environment in traditional English Language Teaching (ELT) classrooms, language experts advocate for the implementation of an interactive approach to enhance the effectiveness of education for learners. The interactive classroom encompasses various elements, including active participation in the learning process, active engagement in the exchange of ideas, and active involvement in communication with teachers. From the perspective of authority, learners are motivated to express their views, practises, and patterns of behaviour. Linguistic challenges are encountered by learners, necessitating their engagement in discussions with peers and educators in order to surmount these intricacies. The process of interaction fosters the development of innovative learning, since learners are able to effectively address psychological hurdles by engaging with others. The objective of this study is to examine the application of an interactive method in the English Language Teaching (ELT) classroom and to analyse the prevailing scenario of interactive education in Bangladeshi educational institutions.